1992
DOI: 10.1002/eji.1830221016
|View full text |Cite
|
Sign up to set email alerts
|

Activated human T cells express a ligand for the human B cell‐associated antigen CD40 which participates in T cell‐dependent activation of B lymphocytes

Abstract: To identify the ligand for the B cell-associated antigen CD40, we constructed a chimeric immunoglobulin molecule where the extracellular portion of the CD40 protein replaced the normal immunoglobulin variable region. No binding was detected on resting peripheral blood T cells. However, following T cell activation with phorbol esters and ionomycin, the chimeric protein bound specifically to activated human T cells and precipitated a 35-kDa protein from such cells. The induction of the CD40 ligand was detectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
200
2
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(218 citation statements)
references
References 31 publications
14
200
2
2
Order By: Relevance
“…Recently Shoker et al (32) demonstrated heightened CD154 gene expression in CD4+ T-lymphocytes during acute and chronic renal rejection, which correlated with the severity of rejection. In contrast to other reported results they demonstrated constitutive CD154 gene expression in PBMCs (12,(33)(34)(35)(36)(37).…”
Section: Discussioncontrasting
confidence: 99%
“…Recently Shoker et al (32) demonstrated heightened CD154 gene expression in CD4+ T-lymphocytes during acute and chronic renal rejection, which correlated with the severity of rejection. In contrast to other reported results they demonstrated constitutive CD154 gene expression in PBMCs (12,(33)(34)(35)(36)(37).…”
Section: Discussioncontrasting
confidence: 99%
“…These mechanisms probably serve to focus productive cognate contact-dependent CD40L+, CD4+ T cell interactions with appropriate target cells. However, CD40L expression may not be limited to CD4+ T cells since studies indicate that CD8+ T cells (41,44), mast cells (49, eosinophils (46), and B cells (47) also can express CD40L. Moreover, there is increased CD40L expression on peripheral blood CD4+ T cells, CD8+ T cells, and B cells in active SLE (48).…”
Section: Discussionmentioning
confidence: 99%
“…T cell activation results in upregulation of CD40L expression [108][109][110], as well as upregulation of FasL expression [8], . As much as engagement of (constitutively expressed) B cell CD40 is necessary for T-dependent stimulation, CD40 triggering also upregulates Fas expression, and engagement of B cell Fas by T cell FasL initiates apoptotic events.…”
Section: Speculative Role For Fas-resistancementioning
confidence: 99%